PCV‐VG combined individualized PEEP determination in one‐lung ventilated patients with PEEP step change direction: A randomized controlled trial - Guowei Li; Saixian Ma; Qian Shu; Zhuhong Fang; Zhiwen Yan; Bo Si (The Clinical Respiratory Journal, 2024)
Abstract Introduction The efficacy of pressure‐controlled volume‐guaranteed ventilation (PCV‐VG) combined with a gradient‐directional change in positive end‐expiratory pressure (PEEP) during one‐lung ventilation (OLV) in patients who underwent thoracoscopic surgery was investigated. Methods Ninety patients were randomly divided into the PC (PCV‐VG + 5 cm H2O fixed PEEP), PI (PCV‐VG + incremental PEEP titration), and PD (PCV‐VG + decremental PEEP titration) groups. Hemodynamic (heart rate [HR] and mean arterial pressure [MAP]), respiratory mechanics (Ppeak, Pmean, and Cdyn), and arterial blood gas (pH, PaCO2, PaO2, and PaO2/FiO2) indices were evaluated at T1 (10 min of two‐lung ventilation [TLV]), T2 (10 min of OLV), and T3 (10 min of recovery, TLV). Enzyme‐linked immunosorbent assay was performed to detect neutrophil elastase (NE), clara cell secretory protein (CC16), and interleukin‐8 (IL‐8) levels at T1 and T3. Results At T2 and T3, Ppeak was lower in the PI and PD groups than in the PC group, while Pmean and Cdyn were higher than in the PC group. Ppeak in the PD group was lower than that in the PI group; however, Pmean was higher at T2 and T3 (P < 0.05). At T2, PaO2 and PaO2/FiO2 were higher, but PaO2/FiO2 and VD/VT were lower in the PD and PI groups than in the PC group (P < 0.05). NE, CC16, IL‐6, and IL‐8 levels were elevated in all three groups at T3, but the PI and PD groups had lower levels than the PC group (P < 0.05). The incidences of postoperative pulmonary complications (PPCs) and surgical intensive care unit hospitalizations in the PD and PI groups were much lower. Conclusion Gradient‐directed altered PEEP titration could improve respiratory mechanics, arterial blood gases, and inflammatory responses and reduce the incidence of PPCs in patients undergoing thoracoscopic surgery.